Preparation and mechanism research on hydrophobic coupling modification of HTV silicone rubber - Li, Qiang; Lei, Mingdong; Li, Ziyou; Gan, Qiang; Sun, Yong; Wei, Xiaoxing (Frontiers in Materials, 2024)
The neat high temperature vulcanized silicone rubber (HTV SR) showed bad hydrophobicity due to the existence of large number of inorganic reinforcing fillers on its surface, which affected its security application in outdoor insulation systems. In this work, hydrophobic silane chains were grafted onto the surface of inorganic particles on the skin layer of HTV SR by one step coupling modification to improve its hydrophobicity. The effects of coupling agent types and coupling reaction conditions on the hydrophobicity of HTV SR were investigated. It was determined that the perfluorooctane trichlorosilicon with a large number of low surface energy fluorine atoms was the preferred coupling agent. The contact angle of HTV SR was increased by 15.70% when the optimal coupling reaction condition was determined to be 60 o C reaction temperature, 4 h reaction time and 0.5% amount of coupling agent. The study found that there are both etching reaction and grafting reaction occurred during the whole coupling modification process, which led to the disappearance or decrease of the lot of holes on HTV SR surface. After the fluorination coupling reaction, the surface of HTV SR became smooth and dense which led the decrease of water absorption. The result of FTIR analysis showed the formation of C-F bond of HTV SR after fluorination modification and the EDS analysis showed that the fluorine content on the surface of fluorinated HTV SR increased significantly. Moreover, the stability analysis showed that the fluorinated HTV SR still had a good thermal stability and mechanical property stability.